PARE0016 IMPACT OF AXIAL SPONDYLOARTHRITIS ON PATIENTS' PROFESSIONAL LIFE: RESULTS FROM THE ONLINE SURVEY EMAS OF 638 FRENCH PATIENTS. (June 2019) - Grange, Laurent; Claudepierre, Pascal; Flipo, René-Marc; Garrido-Cumbrera, Marco; Desfleurs, Emilie; Launois, Francoise Alliot; Gossec, Laure
Abstract : Background: Axial spondyloarthritis (axSpA) can result in functional limitation and work disability. However, there are little data in the era of biologics. Objectives: The aim of this analysis was to evaluate the impact of axSpA on professional life. Methods: Between December 2017 and February 2018, patients followed for axSpA by their rheumatologists or affiliated to the French patients association AFLAR, and self-reporting axSpA, participated in the European Map of Axial Spondyloarthritis (EMAS) cross-sectional patient survey1. Socio-demographics (age, gender, relationship status, educational level, job status), disease activity (BASDAI) and the impact of axSpA on professional life (job choice, working hours, sick leave, unemployment and relationship with colleagues) were collected. The participants who were employed and working at the time of the survey were regrouped as "employed" and the ones employed or on temporary sick leave or students at the time of the survey as "active". No imputation of missing data was performed and the analyses were descriptive. Results: In France, 638 persons (mean age 41.5 ± 11.1 years, 77% females, mean disease duration 6.9±8.2 years, mean BASDAI 5.9±1.7) participated to the survey. About half of them (51%) had a university degree. At the time of the survey, 54% were employed, 26% in temporary or permanent sick leave, 7% unemployed, 6% retired, 5% homemaker and 2% students. Overall, 176 (28%) received social compensation for handicap or disability due to their axSpA. Regarding the employed ones (n=331), 50% were unskilled workers, 15% had an intermediate profession and 23% a white-collar job. The majority (73%) reported working issues related to axSpA in the last 12 months, such as sick leave (60%), reducing or difficulties to fulfill working hours (62%) or missing working hours for health appointments (33%). Among patients on temporary sick leave (n=72), 92% reported that it was the consequence of their axSpA and the mean duration of their temporary sick leave in the last 12 months was 5.4±4.0 months. Considering active people (n=418), 39% declared that their relationships with their work colleagues were worse since their axSpA. AxSpA had also influenced 55% of them in their job choice and drove 44% to adapt their workplace and 34% to move to another job. Finally, 62% expressed their fear to lose their job because of axSpA. Conclusion: In this survey of 638 young axSpA patients, 66% of participants were active; the impact of the disease on professional life was described as important and often had consequences including permanent sick leave or unemployment. These aspects of axSpA should be better assessed. Reference: [1] Gossec L, et al. Diagnostic Delay and Associated Factors in Axial Spondyloarthritis across Europe. Results from the European Map of Axial Spondyloarthritis Survey. Arthritis Rheumatol. 2018 Sep;70 Suppl 9:688 Acknowledgement: Survey supported by Novartis Disclosure of Interests: LAURENT GRANGE Consultant for: Laurent Grange has received honoraria from Amgen, Lilly and UCB and research support from Lilly, Amgen, UCB, Expanscience, Mylan, Roche diagnostics and TEVA, Pascal Claudepierre Consultant for: Honoraria from Novartis as steering committe of this survey, René-Marc Flipo Consultant for: Honoraria from Novartis as steering committe of this survey, Marco Garrido-Cumbrera Consultant for: Honoraria from Novartis as steering committe of this survey, Emilie Desfleurs Employee of: Employee of Novartis Pharma, Francoise Alliot Launois: None declared, Laure Gossec Grant/research support from: AbbVie, BMS, Celgene, Janssen, Lilly, MSD, Novartis-Sandoz, Pfizer, Sanofi, and UCB, Consultant for: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Nordic Pharma, Novartis-Sandoz, Pfizer, Roche, Sanofi, and UCB, Consultant for: L Gossec has received honoraria from Celgene as investigator for this study